Policy Dialogue on Engagement of Regional Economic Communities in Enhancing Regional Agricultural Trade and Early Action for Climate Change in Eastern and Central Africa - Recha, John W.M.; Barungi, Julian; Olang'o, Nelson O; Ajayi, Michael T; Radeny, Maren A.O. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Africa is on the brink of a significant demographic shift, with its population projected to double by 2050. This demographic change poses a tremendous challenge in terms of ensuring food security and sustainability for future generations. The vulnerabilities in Africa's food systems, including climate change, population growth, limited resource access, and inadequate infrastructure, underscore the need for resilient food systems. Resilient food systems are designed to withstand shocks and stresses, ensuring stable food production, distribution, and access. Building resilient food systems enhances Africa’s capacity to overcome challenges and provide adequate, nutritious food for its growing population.